Impact of Postharvest Processing on the Metabolite Profile of Arabica Green Coffee Beans - Zainal, Putri Wulandari; Cherie, Dinah (Jurnal Keteknikan Pertanian, 2025)
Postharvest techniques greatly affect the composition and quality of green coffee beans by altering some primary and secondary metabolites. This study aimed to assess the impact of three postharvest processing techniques (natural, honey, and fully washed) on the phenolic compounds, antioxidant activity, caffeine, protein, and color in Arabica green coffee beans from Solok Regency, Indonesia. Spectrophotometric and colorimetric analyses were performed. Data were analyzed using Duncan’s multiple range test, multivariate PCA, and heatmap clustering. Results showed that honey process had the highest polyphenol content of 3918.61 ± 349.85 mg GAE/g, whereas beans that were fully washed had the highest antioxidant activity (1.41 ± 0.21%) and caffeine content (1.41 ± 0.21%). Natural processing yielded the highest protein content (24.26 ± 0.40%). There were significant differences in the hue angle that were related to some of the biochemical differences among the treatments. This research emphasizes the importance of postharvest processing in defining the metabolite profile and quality features of green coffee beans. These findings can assist in formulating the processing steps to be used in refining coffee and maximizing its health-related advantages.